EVALUATION OF THE FATIGUE RESPONSE OF POLYESTER YARNS AFTER THE APPLICATION OF ABRUPT TENSION LOADS - Emilio Luiz Vieira Louzada; Carlos Eduardo Marcos Guilherme; Felipe Tempel Stumpf (Acta Polytechnica CTU Proceedings)
The discovery of oil fields in deeper waters through out the last decades has led the oil industry to the necessity of replacing the mooring systems of offshore platforms from steel to synthetic cables. Consequently, both the industry and the academy started to join forces in order to better understand the mechanical behavior of such materials when subjected to different service conditions. This work aims to assess the change in the fatigue life of polyester (PET) yarns if the material is submitted to an abrupt tension load prior to the application of the fatigue cycling. It was found that the fatigue life of the yarns tested are substantially reduced if the specimen is subjected to this kind of abrupt load in comparison to virgin samples.